Graduate student identity: Negotiating the academic and creative through resistance or conformity. Issue 1 (1st March 2019) - Filiault, Deanna; Gerardi, Debbie; Aguirre, Ryan; Shields, Sara Scott
Identity is not restricted to a single facet of one's personality; a person's identity represents the entirety of who they are and the meanings they provide themselves as it relates to society. In other words, '[p]eople possess multiple identities'. Therefore, identity theorists explore the various roles that people provide themselves and what each of their identities means. As doctoral art/music education students – as it relates to this article – we are most concerned with the ways in which graduate students navigate the duality of their creative and academic identity while conforming to or resisting institutional expectations. The purpose of this study is to understand how Ph.D. art and music education students negotiate their academic and creative identities to resist or conform to expectations within the context of academic norms. This study sought to answer the following research question: to what extent are professional graduate arts education students navigating dual, overlapping creative and academic identities?